Navigating talent scarcity: talent attraction and selection practices among domestic firms and multinational corporations in Saudi Arabia - Alhaider, Masoud; Ali, Sa’ad; Abushaikha, Ismail (Emerald, 2025)
Purpose The study aimed to identify factors affecting talent attraction and selection in Saudi Arabia’s private sector and to compare the practices of domestic firms (DFs) and multinational corporations (MNCs). Design/methodology/approach Qualitative data were collected through semi-structured interviews and archival evidence from three DFs and 3 MNCs in Saudi Arabia. Data was analyzed using thematic analysis. Findings Integrating institutional logics and dynamic capabilities theory, this study develops a novel framework explaining how firms manage a talent-starved environment. Unlike traditional models that emphasize targeting “ready-to-go” talent, our findings reveal that firms increasingly seek individuals with potential, balancing institutional pressures and business needs. MNCs and DFs alike must exercise strategic dexterity – sensing environmental shifts, seizing emerging opportunities, and reconfiguring selection criteria – by either merging existing logics or adopting new ones. Practical implications Although MNCs have been practicing formalized talent attraction and selection for longer than DFs and have more sophisticated processes, both organizational types have scope for improving their practices in the context of institutional logics at play in Saudi Arabia. Originality/value This study advances the understanding of talent attraction and selection in the Middle East by empirically demonstrating how institutional logics shape human resource practices in Saudi Arabia. It also applies a dynamic capabilities perspective to explain differences between DFs and MNCs, highlighting how firms strategically adapt talent management practices to labor market constraints.
Keywords: Talent attraction; Talent selection; Institutional logics; Dynamic capabilities; Wasta informal network; Saudi Arabia; 35 Commerce, Management, Tourism and Services; Industrial Relations; 3505 Human resources and industrial relations; 3507 Strategy, management and organisational behaviour